Some Results on Strongly Fully (m,n)- Stable Modules to Ideal - Al-Hassani, Uhood (Iraqi Journal of Science, 2023)
Let R be a commutative ring with non-zero identity element .For two fixed positive integers m and n , a right R-module M is called strongly fully (m,n)- stable relative to an ideal A of R n x m if θ (N)⊆ N ∩ Mn A for each n- generated submodule of Mm and R- homomorphism θ :N→ Mm. In this paper I give some characterizations theorems and properties of strongly fully (m,n) –stable modules relative to an ideal A of R n x m.